STRUKTUR POPULASI REKRUT KARANG HERMATIFIK PADA METODE FISH HOME DI TELUK PALU - Salanggon, Alismi M; Finarti, Finarti (Sekolah Tinggi Perikanan dan Kelautan (STPL) Palu, 2016)
The goals of this research were to study the characteristics of coral recruits on Fish Home artificial reef modules at two sites with different environmental characteristics (habitat condition, physical and chemical water quality). The research was carried out from July to September 2016 at Mamboro Suburb in Palu Bay and Lero Village in Donggala District. Data were collected using SCUBA via a systematic random sampling method. Coral recruits were identified and community composition indices of abundance, distribution, diversity, evenness and dominance calculated. Water quality parameters were conducive to coral growth. The artificial substrate (fish homes) enabled coral settlement. Corals recruited mostly onto the outer walls of the fish homes, and were evenly distributed. At the Lero site, 683 colonies were counted, comprising 11 Families and 33 Genera, at Mamboro 563 colonies comprised 13 Families and 31 Genera. Dispersal patterns of the dominant group, no dominant species, average diversity and evenness.